DAMPAK PROGRAM PENGEMBANGAN KECAMATAN (PPK) TERHADAP PENINGKATAN EKONOMI MASYARAKAT DI KECAMATAN BANTIMURUNG KABUPATEN MAROS - Adi Sumandiyar (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2013)
The research conducted in Bantimurung District of Maros Regency aims to (1) analyze the impact of the Kecamatan Development Program (PPK) on the improvement of family income and increased job opportunity in Ban timurung District of Maros Regency, and (2) describe strategies for people economic improvement. Data were collected through field surveys by interviewing 100 people receiving community revolving fund loan of the Usaha Ekonomi Produktif (UEP) (=Productive Economic Business) and the Women’s Group Savings and Loans (SPP) as respondents who were selected by using cluster random sampling method from 8 villages/sub-district in Bantimurung District of Maros Regency. Descriptive analysis of pre and post design and SWOT analysis were used. The result suggests that the program gives a positive and significant impact for the community in terms of the improvement of family income and increased job opportunities. However, there are a number of people who have not been able to increase their revenue and still unemployed. In order to improve the local economy, strategies such as development of natural resources and improvement of people’s skills for technological adaptation are needed.Keywords: Income Family, Employment, Technology Adaptation